Matrimonial Practices among Muslims of Pokhara - Ojha, Niranjan (Kalika Journal of Multidisciplinary Studies, 2022)
Study of religious minorities keeps greater importance in a country like Nepal, where Hindus constitute the majority of the population. Marriage is a normal societal phenomenon and common in Nepali society. Muslims marriage is curious and not common to the majority religious group of Nepal. Marriage is a contract between bride and groom for the purposes of legal intercourse, child propagation, and the social contract between husband and wife. Muslims perform their marital rituals according to Sariat. The marriage of Muslims is directed by the faith itself, according to the Holy Quran. Muslim marriage has long been curious to non-Muslims because of its uniqueness. As a result, an attempt has been made to address this issue. This article is based on qualitative research and aims to outline the critical measures to be taken throughout marriage. To generalize the subject, an observation approach, in[1]depth interviews and library research are being used. As responders for the goal of gathering knowledge, Muslim scholars, masjid Committee Members, Moulana and elderly people from Miya Patan of Pokhara who have witnessed such rites were chosen. Because they desired anonymity, the responders are referred to as Res. 1. , Res.2., Res.3, Res.4 and so on. This research looks on Muslim marriage, a unique and traditional marital practice in Nepal. It makes an attempt to address the general situation of Muslim marital practice in Miya Patan of Pokhara. In Nepal, particularly in Pokhara, people have forgotten the value of marriage in the name of modernization. Muslims of Pokhara have protected the society's social standards and cultural values of marriage which should be learn from them.